Addenda and errata: Crystal structure of (E)-N-(3, 4-dimethoxybenzylidene)morpholin-4-amine. Corrigendum. (January 2015) - Çelikesir, S. T.; Akkurt, M.; Jarrahpour, A.; Chermahini, M. M.; Büyükgüngör, O.
No abstract available